البيئة ودورها في تعزيز السلم العالمي - لطالي مراد; رزيق عمار (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
في خضم بحثه عن حلول قانونية للمشكلة البيئية، وجد المجتمع الدولي نفسه أمام فرصة سانحة لتوحيد الجهود الدولية تحت سقف واحد للتصدي لهذه المشكلة. والتي تبعا لخصوصيتها من سعة الانتشار وشدة الآثار فرضت ضرورة التعاون والتنسيق الدولي، وذلك باستخدام الآليات القانونية الدولية الحمائية منها: التعاون المشترك والتنسيق وتبادل المعلومات وتقديم المساعدات التقنية والمادية وتقاسم المسؤولية على أساس التباين. كل هذه الآليات وغيرها خدمت بطريقة أو بأخرى مسألة السلم العالمي وعززت من صنع فرص السلام حتى بين الفرقاء السياسيين والايديولوجيين، على الأقل من حيث المبدأ في انتظار تجسيد ذلك ميدانيا وتنفيذ الالتزامات بحسن نية في هذا المجال. Abstract: In the midst of its long search for legal solutions to its environmental problem, the international society found an opportunity to unite international efforts under one roof to tackle this issue; which is special and fast spreading with important effects that mandated international cooperation and coordination by way of using international law mechanisms of protection like: collective cooperation, coordination, information exchange, providing technical and material help and sharing responsibility. All of this mechanisms and others were helpful for world peace matter and promoted peace opportunities even amongst political and ideological rivals, at least in principle pending concretisation and implementation of obligations with good intentions